The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/mmr.2018.9735
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a DNA vaccine encoding Brucella BvrR in BALB/c mice

Abstract: Brucellosis is an important neglected zoonotic disease, and the pathogens responsible are Brucellae. In order to evaluate the immunogenicity and protective efficacy of a DNA vaccine encoding Brucella BvrR, the recombinant plasmid pCDNA-BvrR was constructed by inserting the BvrR gene fragment into a pCDNA3.0 vector. The His 6-tagged BvrR was purified with His-trap FF crude affinity chromatography and verified with an anti-histidine monoclonal antibody by western blot analysis. The specific immunoglobulin antige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A limitation in this study is the selection of hypovirulent strain B. abortus S19 as challenge strain for protection experiments [ 43 , 71 , 72 ]. B. abortus S19 was originally isolated as a virulent strain from a Jersey cow in 1923 and was found to become attenuated after being kept in the laboratory at room temperature for more than a year [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation in this study is the selection of hypovirulent strain B. abortus S19 as challenge strain for protection experiments [ 43 , 71 , 72 ]. B. abortus S19 was originally isolated as a virulent strain from a Jersey cow in 1923 and was found to become attenuated after being kept in the laboratory at room temperature for more than a year [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…DNA-based vaccines contain gene sequences of pathogens, which are essential for intracellular survival of Brucella spp. The immunogenicity and efficacy of these virulence genes used in DNA vaccines have been demonstrated in animal studies, including the two-component BvrR/BvrS system ( 119 ), Cu-Zn superoxide dismutase (SOD) ( 126 , 140 ), ribosomal L7/L12 or Brucella lumazine synthase (BLS) ( 139 , 141 ), B. melitensis omp31 and omp25 genes ( 125 , 142 ), antigenic surface protein (BCSP31) gene ( 120 ), SP41 ( 143 ), and ribosomal protein L9 (rL9) ( 122 ). According to the studies that have been done, DNA vaccines may have the ability to resolve the disadvantages of other brucellosis vaccines ( 119 , 120 , 144 ).…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…The immunogenicity and efficacy of these virulence genes used in DNA vaccines have been demonstrated in animal studies, including the two-component BvrR/BvrS system ( 119 ), Cu-Zn superoxide dismutase (SOD) ( 126 , 140 ), ribosomal L7/L12 or Brucella lumazine synthase (BLS) ( 139 , 141 ), B. melitensis omp31 and omp25 genes ( 125 , 142 ), antigenic surface protein (BCSP31) gene ( 120 ), SP41 ( 143 ), and ribosomal protein L9 (rL9) ( 122 ). According to the studies that have been done, DNA vaccines may have the ability to resolve the disadvantages of other brucellosis vaccines ( 119 , 120 , 144 ). In most studies, animals vaccinated with different types of DNA vaccines have shown full protection against virulent strains (e.g., B. abortus S19, B. abortus 2308, B. melitensis 16M , and B. melitensis Rev1 ) ( 120 , 143 ).…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…In animal models it has been observed that T4SS is necessary for the onset of the infection (102). Recently it has been published that BvrR is a good candidate for a DNA vaccine in the murine brucellosis model, but many studies are missing (103).…”
Section: Antigenic Components Of Brucella As Virulence Factorsmentioning
confidence: 99%